Extrusion limit diagram of Mg–5Bi–3Al–1Zn alloy and effects of extrusion parameters on its microstructures and mechanical properties - Qinghang Wang; Li Wang; Jiaze Xu; Haowei Zhai; Yang Chen; Shouxin Xia; Xu Qin; Yongfei Li; Bin Jiang; Daolun Chen (Journal of Materials Research and Technology, 2024)
Hot-compressive tests and finite element simulations were carried out to construct an extrusion limit diagram of a Mg–5Bi–3Al–1Zn (wt.%) alloy in this work. It was observed that 310 °C became a dividing line, below which the safe extrusion zone was narrow because the stress required to induce the plastic flow of alloy was higher than the pressure limit. Once the temperature exceeded this critical temperature, a wide safe extrusion zone controlled by the cracking limit was attained. The theoretical maximum ram extrusion speed was calculated as approximately 48 mm/s at 310 °C. No hot cracks occurred on the surface of alloys extruded at 30 and 44 mm/s; while at 56 mm/s, obvious orange peel defects were observed. Through further microstructural observation, the 44 mm/s extruded alloy exhibited a complete dynamic recrystallization structure with an average grain size of 21.9 μm, along with a relatively weak basal fiber texture (with a maximum pole intensity of 5.8) and plentiful nano-Mg3Bi2 phases. These microstructure features led to superior tensile properties (namely a tensile yield strength of 270 MPa, an ultimate tensile strength of 375 MPa and an elongation of 15%) at the high-speed extrusion.